Zircon geochemistry of felsic gneisses from Harvey Nunatak, Napier Complex in East Antarctica - Takehara, Mami; Horie, Kenji; Hokada, Tomokazu (2023)
The 14th Symposium on Polar Science/Ordinary sessions [OG] Polar geosciences, Wed. 15 Nov. / Entrance Hall (1st floor), National Institute of Polar Research conference object